2016
DOI: 10.1038/srep31079
|View full text |Cite
|
Sign up to set email alerts
|

A VEGF-dependent gene signature enriched in mesenchymal ovarian cancer predicts patient prognosis

Abstract: We have previously reported surrogate biomarkers of VEGF pathway activities with the potential to provide predictive information for anti-VEGF therapies. The aim of this study was to systematically evaluate a new VEGF-dependent gene signature (VDGs) in relation to molecular subtypes of ovarian cancer and patient prognosis. Using microarray profiling and cross-species analysis, we identified 140-gene mouse VDGs and corresponding 139-gene human VDGs, which displayed enrichment of vasculature and basement membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…Moreover, we investigated transcription factors included in the 97-gene signature. Consistent with previous studies, p53 35 , 36 and HIF1α 22 were the upregulated transcription factors. However, a previous study reported that a large phase III trial of adenoviral wild-type p53 delivery combined with taxol and carboplatinum did not show any positive results in ovarian cancer 37 .…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, we investigated transcription factors included in the 97-gene signature. Consistent with previous studies, p53 35 , 36 and HIF1α 22 were the upregulated transcription factors. However, a previous study reported that a large phase III trial of adenoviral wild-type p53 delivery combined with taxol and carboplatinum did not show any positive results in ovarian cancer 37 .…”
Section: Discussionsupporting
confidence: 92%
“…As regards tumour VEGF levels, the only evidence was that elevated VEGF levels (tVEGF) had a negative impact on patient survival at early stages [71]. More recent genomic signature studies, including multiple genes related to this pathway, confirm the adverse prognostic value of elevated VEGF expression levels [72].…”
Section: Angiogenesis-related Biomarkersmentioning
confidence: 99%
“…The overexpression of c-Myc proteins probably promotes the process of malignant change and progression of tumor [ 20 , 21 ]. Therefore, the Myc family is an excellent target for anti-cancer therapeutics [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis is a crucial feature of EOC pathogenesis [ 22 ]. Vascular endothelial growth factor (VEGF) is the most important angiogenesis promoter [ 23 , 24 ]. VEGF protein has been consistently associated with EOC progression [ 23 , 25 ].…”
Section: Discussionmentioning
confidence: 99%